Preparation method and application of iron-rich charcoal-ardealite composite material

By preparing iron-rich biochar-phosphorogypsum composite materials, the shortcomings in cadmium adsorption capacity and selectivity of protozoa biochar are solved, and more efficient cadmium adsorption and easy recovery are achieved.

CN119588309APending Publication Date: 2025-03-11WUHAN UNIV OF SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411601548.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The adsorption capacity of protoplastic biochar is not ideal when removing cadmium, and lacks selectivity in complex environmental media, which affects the removal effect.

Method used

The preparation method of iron-rich biochar-phosphogypsum composite material is adopted, and the iron element is loaded through the reaction of straw straw with FeSO4·7H2O solution, and then co-pyrolyzed with phosphogypsum to form biochar with richer oxygen-containing functional groups and impart it with magnetism.

Benefits of technology

The adsorption capacity of biochar is improved, especially in adsorbing heavy metal cadmium, and is convenient for separation and recovery from water due to its magnetic properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119588309A_ABST
    Figure CN119588309A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of an iron-rich charcoal-ardealite composite material, and belongs to the technical field of environmental engineering, and the preparation method comprises the following steps: selecting straw stalks as a raw material, and grinding the straw stalks to 150-mesh fineness; the ground straw stalks are put into a FeSO4. 7H2O solution to be soaked; after soaking is finished, the straw is dried, and iron-rich straw stalks are obtained; the method comprises the following steps: uniformly mixing iron-rich straw stalks with ardealite, placing the mixture in a vacuum tube furnace under a nitrogen protective atmosphere, carrying out heating pyrolysis, and then naturally cooling or forcibly cooling to room temperature; soaking iron-rich charcoal-ardealite obtained after pyrolysis in a NaOH solution again, and then washing with water until the pH value is neutral; and finally, carrying out drying treatment on the cleaned iron-rich charcoal-ardealite. According to the preparation method and application of the iron-rich biochar-ardealite composite material adopting the structure, the adsorption capacity of the composite material during adsorption of heavy metal cadmium is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmental engineering technology, and in particular to a preparation method and application of an iron-rich biochar-phosphogypsum composite material. Background Art

[0002] As an adsorption material, biochar has shown potential application value in removing heavy metals such as cadmium (Cd) from water and soil. Biochar has potential in removing cadmium because of its large specific surface area, rich oxygen-containing functional groups, high porosity, and wide source of biochar materials, high efficiency and low cost.

[0003] However, the adsorption capacity of raw biochar for cadmium is not ideal, and it is not realistic to invest in large-scale wastewater treatment of cadmium. In complex environmental media, such as those containing multiple metal ions and other pollutants, raw biochar may not have high selectivity to specifically adsorb cadmium, but will also adsorb other cations or anions at the same time, affecting the removal effect. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method and application of an iron-rich biochar-phosphogypsum composite material to solve the above-mentioned problems.

[0005] To achieve the above object, the present invention provides a method for preparing an iron-rich biochar-phosphogypsum composite material and application thereof, which specifically comprises the following steps: S1. Raw material preparation: Select rice straw as raw material and grind it to a fineness of 150 mesh; S2. Iron loading: The ground rice straw was placed in 0.8 mol / L FeSO 4 7H 2 Immerse in O solution; S3, drying: after the soaking is completed, the straw is separated by filtering, and the straw is dried to obtain iron-rich rice straw; S4, pyrolysis: take a portion of the dried iron-rich rice straw, mix the iron-rich rice straw with phosphogypsum evenly, place the mixed materials in a vacuum tube furnace under a nitrogen protective atmosphere, and perform pyrolysis at a high temperature. After the pyrolysis is completed, the temperature is naturally cooled or forced to cool to room temperature, i.e., 25°C; S5. Alkali treatment: the iron-rich biochar-phosphogypsum obtained after pyrolysis is soaked again in a 2 mol / L NaOH solution, and then washed with water until the pH value of the waste liquid reaches neutral; S6. Final drying: The last step is to dry the cleaned iron-rich biochar-phosphogypsum to obtain the finished product of iron-rich biochar-phosphogypsum.

[0006] Preferably, in the above-mentioned method for preparing an iron-rich biochar-phosphogypsum composite material and its application, the rice straw and FeSO in step S2 4 7H 2 The solid-liquid ratio of the O solution was set to 1:5, that is, 5 ml of solution corresponded to each gram of straw, the soaking temperature was room temperature, and the soaking time was 24 hours.

[0007] Preferably, in the above-mentioned method for preparing and applying the iron-rich biochar-phosphogypsum composite material, the drying condition in step S3 is drying at 70° C. for 48 hours.

[0008] Preferably, in the above-mentioned method for preparing and applying the iron-rich biochar-phosphogypsum composite material, the mass ratio of the iron-rich rice straw and the phosphogypsum mixed in step S4 is 2:1.

[0009] Preferably, in the preparation method and application of the above-mentioned iron-rich biochar-phosphogypsum composite material, the vacuum tube furnace in step S4 is heated to 600°C at a rate of 10°C / min, and the mixture of iron-rich rice straw and phosphogypsum is pyrolyzed at this temperature for 2 hours.

[0010] Preferably, in the preparation method and application of the above-mentioned iron-rich biochar-phosphogypsum composite material, the solid-liquid ratio of the iron-rich biochar-phosphogypsum and the NaOH solution in step S5 is 1:5, and the soaking time is 24 hours.

[0011] Preferably, in the preparation method and application of the above-mentioned iron-rich biochar-phosphogypsum composite material, the drying condition in step S6 is to dry the cleaned iron-rich biochar-phosphogypsum at 70° C. for 24 hours.

[0012] Preferably, in the preparation method and application of the above-mentioned iron-rich biochar-phosphogypsum composite material, the obtained iron-rich biochar-phosphogypsum is used to treat cadmium-containing wastewater.

[0013] Therefore, the present invention adopts a preparation method and application of an iron-rich biochar-phosphogypsum composite material of the above structure, and uses two raw materials for co-pyrolysis, so that the quantity and quality of biochar are improved, and the composite biochar has richer oxygen-containing functional groups. By imparting magnetism to the prepared composite material, the composite material is easy to recycle during reuse, thereby solving the shortcoming of the difficulty in recycling powdered material resources. The present invention adopts a biochar-phosphogypsum composite material prepared by pyrolysis technology, and the preparation method is simple and feasible, and it is easy to large-scale industrial production; the composite material has excellent adsorption capacity when adsorbing heavy metal cadmium; and the composite material is magnetic and easy to separate from the water body.

[0014] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The SEM and EDS images of BC and BC-PG of a preparation method and application example of an iron-rich biochar-phosphogypsum composite material of the present invention; Figure 2 FTIR graphs of BC and BC-PG in a preparation method and application example of an iron-rich biochar-phosphogypsum composite material of the present invention; Figure 3 XRD diagrams of BC and BC-PG in a preparation method and application example of an iron-rich biochar-phosphogypsum composite material of the present invention; Figure 4 It is a VSM diagram of BC and PG-BC of a preparation method and application example of an iron-rich biochar-phosphogypsum composite material of the present invention; Figure 5 It is a simulation diagram of the adsorption kinetic model of BC and BC-PG in a preparation method and application example of an iron-rich biochar-phosphogypsum composite material of the present invention; Figure 6 It is a simulation diagram of the isothermal adsorption model of BC and BC-PG in a preparation method and application example of an iron-rich biochar-phosphogypsum composite material of the present invention. DETAILED DESCRIPTION

[0016] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.

[0018] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.

[0019] Example 1 The present application provides a method for preparing an iron-rich biochar-phosphogypsum composite material, which specifically comprises the following steps: S1. Raw material preparation: Select rice straw as raw material and grind it to a fineness of 150 mesh; S2. Iron loading: The ground rice straw was placed in 0.8 mol / L FeSO 4 7H 2 O solution at room temperature for 24 h. 4 7H 2 The solid-to-liquid ratio of O solution was set to 1:5, i.e., 5 ml of solution per gram of straw; S3, drying: after the soaking is completed, the straw is separated by filtration, and the straw is dried at 70° C. for 48 hours to obtain iron-rich rice straw; S4, pyrolysis: take a portion of the dried iron-rich rice straw, mix the iron-rich rice straw and phosphogypsum in a mass ratio of 2:1, place the mixed material in a vacuum tube furnace under a nitrogen atmosphere, heat it to 600°C at a rate of 10°C / min, and pyrolyze the mixture of the iron-rich rice straw and phosphogypsum for 2 hours at this temperature. After the pyrolysis is completed, cool it down naturally or forcefully to room temperature, i.e., 25°C; S5. Alkali treatment: the iron-rich biochar-phosphogypsum obtained after pyrolysis is soaked again in a 2 mol / L NaOH solution, the solid-liquid ratio of the iron-rich biochar-phosphogypsum to the NaOH solution is 1:5, the soaking time is 24 hours, and then washed with water until the pH value of the waste liquid reaches neutral; S6. Final drying: The last step is to dry the cleaned iron-rich biochar-phosphogypsum at 70°C for 24 hours to obtain the finished iron-rich biochar-phosphogypsum.

[0020] The obtained iron-rich biochar-phosphogypsum is used to treat cadmium-containing wastewater.

[0021] Example 2 Weigh 30 mg of material sample iron-rich biochar-phosphogypsum (BC-PG) into a 50 mL conical flask and add 30 mL of 50 mg / L -1 Cd 2+ solution, and the pH value of the solution was adjusted to 6 with NaOH (0.1 M); At 25°C, the temperature was 180 rpm in an oscillator. -1 The rate of oscillation; The supernatant was taken at 5, 15, 30, 60, 120, 240, 480, 720, and 1440 min, and the Cd content in the solution was determined using a flame atomic absorption spectrometer. 2+ concentration; Pseudo-first-order and pseudo-second-order kinetic equations were used for fitting.

[0022] Example 3 Weigh 30 mg of material sample iron-rich biochar-phosphogypsum (BC-PG) into a 50 mL conical flask, and add 30 mL of 5, 10, 20, 40, 80, and 100 mg L -1 CD 2+ Solution; The pH value of the solution was adjusted to 6 with NaOH (0.1 M) and the temperature was set at 180 rmin at 25 °C. -1 Oscillate for 24 hours; After standing, the supernatant was taken and the Cd content in the solution was determined using a flame atomic absorption spectrometer. 2+ concentration; The data were fitted and analyzed using the Langmuir and Freundlich equations.

[0023] Comparative Example 1 The specific steps for preparing iron-rich biochar are as follows: S1, select rice straw as raw material and grind it to a fineness of 150 mesh; S2. Iron loading: The ground rice straw was placed in 0.8 mol / L FeSO 4 7H 2 O solution at room temperature for 24 h. 4 7H 2 The solid-to-liquid ratio of O solution was set to 1:5, i.e., 5 ml of solution per gram of straw; S3, drying: after the soaking is completed, the straw is separated by filtration, and the straw is dried at 70° C. for 48 hours to obtain iron-rich rice straw; S5, alkali treatment: the iron-rich rice straw is soaked again in a 2 mol / L NaOH solution, the solid-liquid ratio of the iron-rich rice straw to the NaOH solution is 1:5, the soaking time is 24 hours, and then washed with water until the pH value of the waste liquid reaches neutral; S6. Final drying: The last step is to dry the cleaned iron-rich rice straw at 70°C for 24 hours to obtain the finished iron-rich rice straw, namely BC.

[0024] The obtained BC is used to treat cadmium-containing wastewater.

[0025] Weigh 30 mg of material sample BC into a 50 mL conical flask and add 30 mL of 50 mgL -1 Cd 2+ solution, and the pH value of the solution was adjusted to 6 with NaOH (0.1 M); At 25°C, the temperature was 180 rpm in an oscillator. -1 The rate of oscillation; The supernatant was taken at 5, 15, 30, 60, 120, 240, 480, 960, and 1440 min, and the Cd content in the solution was determined using a flame atomic absorption spectrometer. 2+ concentration; Pseudo-first-order and pseudo-second-order kinetic equations were used for fitting.

[0026] Weigh 30 mg of material sample BC into a 50 mL conical flask, add 30 mL of BC with initial concentrations of 5, 10, 20, 40, 80, and 100 mg L -1 CD 2+ Solution; The pH value of the solution was adjusted to 6 with NaOH (0.1 M) and the temperature was set at 180 rmin at 25 °C. -1 Oscillate for 24 hours; After standing, the supernatant was taken and the Cd content in the solution was determined using a flame atomic absorption spectrometer. 2+ concentration; The data were fitted and analyzed using the Langmuir and Freundlich equations.

[0027] Comparative analysis of Example 2 and Example 3 with Comparative Example 1 respectively yields the following Tables 1 and 2; Table 1 Fitting parameters of the adsorption kinetic model of BC and BC-PG

[0028] Table 2 Isotherm adsorption model fitting parameters of BC and BC-PG

[0029] From the fitting parameters of the adsorption kinetic model in Table 1, we can evaluate the adsorption rate and adsorption mechanism of BC (iron-rich biochar) and BC-PG (iron-rich biochar-phosphogypsum composite). Two commonly used adsorption kinetic models are mentioned here: pseudo-first-order kinetic model and pseudo-second-order kinetic model. These models help us understand how the process of material adsorption of pollutants changes over time.

[0030] Pseudo-first-order kinetic model BC Equilibrium adsorption capacity (Qe): 30.92 mg / g; Rate constant (k1): 9.847 min -1 ; Correlation coefficient (R²): 0.940; BC-PG Equilibrium adsorption capacity (Qe): 46.57 mg / g; Rate constant (k1): 0.534 min -1 ; Correlation coefficient (R²): 0.950; The pseudo-first-order kinetic model mainly describes the physical adsorption process. From the data, it can be seen that BC-PG has a higher equilibrium adsorption capacity (Qe), which indicates that BC-PG can adsorb more pollutants at the adsorption equilibrium state. However, the rate constant (k1) of BC is higher, which means that its initial adsorption rate is faster. Nevertheless, the R² value of BC-PG is higher, indicating that the pseudo-first-order kinetic model fits the BC-PG adsorption process better.

[0031] Pseudo-second-order kinetic model BC Equilibrium adsorption capacity (Qe): 32.31 mg / g; Rate constant (k2): 0.475 g / mg·min; Correlation coefficient (R²): 0.979; BC-PG Equilibrium adsorption capacity (Qe): 51.62 mg / g; Rate constant (k2): 0.014 g / mg·min; Correlation coefficient (R²): 0.969; The pseudo-second-order kinetic model is suitable for describing adsorption processes involving chemical reactions. Similar to pseudo-first-order kinetics, BC-PG shows a higher equilibrium adsorption amount, which is consistent with the previous conclusion. However, the rate constant (k2) of BC-PG is significantly lower than that of BC, indicating that BC-PG takes longer to reach adsorption equilibrium. Despite this, the R² value of BC-PG is still very high, indicating that the pseudo-second-order kinetic model can fit the data of BC-PG well.

[0032] Therefore, the following conclusions were drawn: Adsorption capacity: BC-PG showed superior adsorption capacity to BC, both in terms of maximum adsorption amount and adsorption efficiency.

[0033] Adsorption rate: Although the equilibrium adsorption capacity of BC-PG is higher, it reaches the equilibrium state slowly. In contrast, the initial adsorption rate of BC is faster.

[0034] Adsorption mechanism: The pseudo-second-order kinetic model provided very good fitting results for both materials, especially for BC-PG, which implied that chemical adsorption played an important role in the adsorption process.

[0035] In summary, BC-PG performed better in terms of long-term stability and maximum adsorption capacity, while BC had an advantage in rapid responsiveness.

[0036] From the isothermal adsorption model fitting parameters in Table 2, we can analyze the adsorption performance of BC (iron-rich biochar) and BC-PG (iron-rich biochar-phosphogypsum composite). Two common isothermal adsorption model parameters are mentioned here: the correlation coefficient and fitting parameters of the Langmuir equation and the Freundlich equation. These parameters help us understand the adsorption capacity of the material and its affinity for pollutants. Here are some performance descriptions based on the given data: Maximum adsorption capacity (Qm): The maximum adsorption capacity of BC is 21.78 mg / g.

[0037] The maximum adsorption capacity of BC-PG was significantly higher, reaching 91.49 mg / g.

[0038] This suggests that BC-PG can theoretically adsorb more target pollutants.

[0039] Langmuir constant (KL): The KL value of BC is 1.50.

[0040] The KL value of BC-PG is 1.95.

[0041] The KL value reflects the binding strength between the adsorbent surface sites and the adsorbate, and a larger KL value means a stronger binding force. Therefore, BC-PG shows a slightly stronger binding force than BC.

[0042] Langmuir correlation coefficient (R²): R² for BC is 0.913; R² for BC-PG is 0.961.

[0043] The R² value close to 1 indicates that the experimental data fits the Langmuir model well, which shows that the two materials show monolayer adsorption characteristics for adsorbates within a certain concentration range. The data fit of BC-PG is better.

[0044] Freundlich constant (KF): The KF value of BC is 10.96; the KF value of BC-PG is 45.96.

[0045] KF represents the adsorption capacity, and the larger the value, the stronger the adsorption capacity. BC-PG has a higher KF value, which further proves that it has stronger adsorption potential.

[0046] Freundlich index (n): The n value of BC is 0.18; the n value of BC-PG is 0.33.

[0047] n values ​​between 0 and 1 usually indicate a favorable adsorption process. The larger the n value, the easier the adsorption process occurs. BC-PG has a higher n value, which means it is easier to adsorb the target substance than BC.

[0048] Freundlich correlation coefficient (R²): R² for BC is 0.980; R² for BC-PG is 0.970.

[0049] Similarly, the R² value close to 1 indicates that the data fit the Freundlich model well, indicating that both BC and BC-PG are suitable for describing the multilayer adsorption behavior.

[0050] In summary, BC-PG showed better adsorption performance than BC, including a larger maximum adsorption capacity (Qm), a higher Freundlich constant (KF) and a better Freundlich index (n), and both of them followed the Langmuir and Freundlich adsorption isotherm models to a certain extent. This means that BC-PG may be a more effective material for removing pollutants from water or soil.

[0051] Figure 1 The scanning electron microscope (SEM) images and energy dispersive X-ray spectroscopy (EDS) images of BC (biochar) and BC-PG (biochar-phosphogypsum composite) are shown in Figure 1. The following is a detailed explanation of these two parts: SEM images BC Microstructure: The SEM image of BC shows a relatively rough surface with obvious granular structure. These particles may be formed by carbonization of different components of the original biomass material.

[0052] BC-PG Microstructure: The SEM image of BC-PG shows a relatively smooth surface, and some fibrous structures can be seen. This may be because the addition of phosphogypsum changes the original biochar structure and forms a new composite material.

[0053] EDS analysis BC Element distribution: EDS results show that BC contains multiple elements such as Mg, Si, Ca and Fe. Among them, the distribution of silicon (Si) and calcium (Ca) is relatively uniform, while the distribution of magnesium (Mg) and iron (Fe) is relatively scattered.

[0054] BC-PG Element distribution: Mg, Si, Ca and Fe were also detected in BC-PG. It is worth noting that the distribution of elements in BC-PG seems to be more uniform than that in BC, which may be because the addition of phosphogypsum promotes the mixing of elements.

[0055] From the above, it can be seen that BC-PG has a smoother surface and a more regular structure than BC, which is related to the role of phosphogypsum in its preparation process. Such surface morphology will affect its adsorption performance, and a smoother surface can reduce certain types of physical adsorption. Both BC and BC-PG contain a variety of elements, which suggests that they may be versatile and can be used for a variety of purposes. In addition, differences in element distribution may also affect their chemical adsorption capacity and selectivity; the distribution of elements in BC-PG is more uniform than that of BC; SEM images and EDS analysis of BC-PG reveal that it has some unique physical and chemical characteristics compared with BC. The more uniform element distribution and smoother surface of BC-PG make it more suitable for adsorption applications in cadmium-containing wastewater.

[0056] Figure 2 This is the FTIR graph of BC and BC-PG. From this FTIR (Fourier transform infrared spectrum) graph, we can observe the following points: -OH peak: at 3500 cm ﹣1 There is a distinct peak on the left and right, which indicates the presence of hydroxyl groups (-OH). The presence of hydroxyl groups usually means that the material is hydrophilic.

[0057] C=O / CO peak: at 1700 cm ﹣1 There is a peak on the left and right, which is the characteristic of carbonyl (C=O) or ester bond (CO). The presence of these functional groups affects the chemical reactivity and stability of the material.

[0058] Si-O-Si peak: at 1100 cm ﹣1 There is a peak on the left and right, which is the characteristic peak of siloxane (Si-O-Si). This indicates that the material contains a siloxane structure, which will affect the mechanical properties and thermal stability of the material.

[0059] Fe-O peak: at 600 cm ﹣1 There is a peak on the left and right, which is the characteristic peak of iron oxide (Fe-O). This indicates that there may be metal oxides in the material, which will affect its magnetism and conductivity.

[0060] By comparing BC and BC-PG, it can be found that the main difference between them lies in the changes of some peaks. For example, BC-PG has a peak at 1700 cm ﹣1 The peak at 1100 cm-1 of BC-PG is more obvious than that of BC, which may indicate that the carbonyl or ester bond content in BC-PG is higher. ﹣1 The peak at is also more obvious than that at BC, indicating that the siloxane content in BC-PG is higher.

[0061] Figure 3 The middle is the XRD graph of BC and BC-PG. This picture shows the X-ray diffraction (XRD) patterns of the two materials (BC and BC-PG). As can be seen from the figure, BC and BC-PG have obvious diffraction peaks in the 2θ angle range, which indicates that they both have a crystalline structure.

[0062] BC: There are obvious diffraction peaks at about 30°, 40°, etc.

[0063] BC-PG: There are similar diffraction peaks in the same angle range, but the intensity and shape may be different.

[0064] The presence of these diffraction peaks indicates that both materials are crystalline and that their lattice structures are similar. By comparing the two spectra, it can be seen that BC-PG has a higher intensity, and a higher intensity generally indicates a better crystallinity of the sample, a higher crystalline phase content, a larger grain size, or a preferred orientation of the sample.

[0065] Figure 4 The figure below is the VSM diagram of BC and BC-PG. This figure shows the mass magnetic susceptibility of the two materials (BC and BC-PG) at different magnetic field strengths. The following points can be seen from the figure: Saturation magnetization: With the increase of the external magnetic field, the mass magnetization of BC and BC-PG first increases rapidly, then tends to be flat and reaches a saturation value. This shows that both materials exhibit ferromagnetism.

[0066] Coercivity: The curve in the figure has an obvious "S" shape bend near the zero magnetic field, which is due to the existence of coercivity. Coercivity is the reverse magnetic field strength required to restore the material from the saturated state to the non-magnetized state. As can be seen from the figure, BC and BC-PG both have a certain coercivity.

[0067] Remanence: When the external magnetic field is zero, BC and BC-PG still retain a certain magnetization intensity, namely remanence, which further confirms their ferromagnetic properties.

[0068] Hysteresis loop: The two curves in the figure form a typical hysteresis loop, indicating that these materials will retain permanent magnetization after experiencing positive and negative magnetic field cycles.

[0069] In summary, both BC and BC-PG show ferromagnetism and have certain coercivity and remanence.

[0070] Figure 5 The figure below is a simulation diagram of the adsorption kinetics model of BC and BC-PG, showing the changes in the adsorption amount of the two materials (BC and BC-PG) at different time points. It can be seen from the figure: BC: In the initial stage, the adsorption amount increases rapidly. As time goes by, the adsorption amount gradually stabilizes.

[0071] BC-PG: The growth rate of adsorption is faster than BC. The time to reach saturation is also shorter than BC.

[0072] This indicates that BC-PG has better adsorption performance, can achieve higher adsorption amount in a shorter time, and reaches saturation faster.

[0073] Figure 6 This is a simulation diagram of the isothermal adsorption model of BC and BC-PG, showing the isothermal adsorption behavior of BC (biochar) and BC-PG (modified biochar) at different concentrations. The following points can be seen from the chart: The adsorption amount increases with the concentration: As the pollutant concentration (Ce) in the solution increases, the adsorption amount (qe) of BC and BC-PG also increases.

[0074] Saturation point: Within a certain concentration range, the adsorption of BC and BC-PG will reach a plateau, indicating that they have approached or reached the maximum adsorption capacity.

[0075] Freundlich and Langmuir model fitting: The Freundlich model is applicable to multilayer adsorption, indicating that the adsorbent surface is not uniform.

[0076] The Langmuir model is applicable to monolayer adsorption and indicates that the adsorbent surface is uniform.

[0077] BC-PG has stronger adsorption capacity: By comparing the two figures, it can be found that BC-PG has a higher adsorption capacity than BC under the same conditions. This may be because the modification process increases its surface area or changes its surface properties, thereby improving the adsorption efficiency.

[0078] In summary, Figure 6 It shows that both BC and BC-PG have good adsorption performance, and the performance of BC-PG is further enhanced by modification.

[0079] Therefore, the present invention adopts a preparation method and application of an iron-rich biochar-phosphogypsum composite material of the above structure, and uses two raw materials for co-pyrolysis, so that the quantity and quality of biochar are improved, and the composite biochar has richer oxygen-containing functional groups. By imparting magnetism to the prepared composite material, the composite material is easy to recycle during reuse, thereby solving the shortcoming of the difficulty in recycling powdered material resources. The present invention adopts a biochar-phosphogypsum composite material prepared by pyrolysis technology, and the preparation method is simple and feasible, and it is easy to large-scale industrial production; the composite material has excellent adsorption capacity when adsorbing heavy metal cadmium; and the composite material is magnetic and easy to separate from the water body.

[0080] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A preparation method and application of an iron-rich biochar-phosphogypsum composite material, characterized in that: The specific steps include: S1. Raw material preparation: Select rice straw as raw material and grind it to a fineness of 150 mesh; S2. Iron loading: The ground rice straw was immersed in a 0.8 mol / L FeSO4·7H2O solution; S3, drying: after the soaking is completed, the straw is separated by filtering, and the straw is dried to obtain iron-rich rice straw; S4, pyrolysis: take a portion of the dried iron-rich rice straw, mix the iron-rich rice straw with phosphogypsum evenly, place the mixed materials in a vacuum tube furnace under a nitrogen protective atmosphere, and perform pyrolysis at a high temperature. After the pyrolysis is completed, the temperature is naturally cooled or forced to cool to room temperature, i.e., 25°C; S5. Alkali treatment: the iron-rich biochar-phosphogypsum obtained after pyrolysis is soaked again in a 2 mol / L NaOH solution, and then washed with water until the pH value of the waste liquid reaches neutral; S6. Final drying: The last step is to dry the cleaned iron-rich biochar-phosphogypsum to obtain the finished product of iron-rich biochar-phosphogypsum.

2. The preparation method and application of an iron-rich biochar-phosphogypsum composite material according to claim 1, characterized in that: In step S2, the solid-to-liquid ratio of the rice straw to the FeSO4·7H2O solution is set to 1:5, that is, 5 ml of solution corresponds to each gram of straw, the soaking temperature is room temperature, and the soaking time is 24 hours.

3. The preparation method and application of an iron-rich biochar-phosphogypsum composite material according to claim 2, characterized in that: The drying condition in step S3 is drying at 70° C. for 48 hours.

4. The preparation method and application of an iron-rich biochar-phosphogypsum composite material according to claim 3, characterized in that: In the step S4, the mass ratio of the iron-rich rice straw to the phosphogypsum is 2:

1.

5. The preparation method and application of an iron-rich biochar-phosphogypsum composite material according to claim 4, characterized in that: In step S4, the vacuum tube furnace is heated to 600° C. at a rate of 10° C. / min, and the mixture of iron-rich rice straw and phosphogypsum is pyrolyzed at this temperature for 2 hours.

6. The preparation method and application of an iron-rich biochar-phosphogypsum composite material according to claim 5, characterized in that: In step S5, the solid-to-liquid ratio of the iron-rich biochar-phosphogypsum and the NaOH solution is 1:5, and the soaking time is 24 hours.

7. The preparation method and application of an iron-rich biochar-phosphogypsum composite material according to claim 6, characterized in that: The drying condition in step S6 is to dry the cleaned iron-rich biochar-phosphogypsum at 70° C. for 24 hours.

8. The preparation method and application of an iron-rich biochar-phosphogypsum composite material according to claim 7, characterized in that: The obtained iron-rich biochar-phosphogypsum is used to treat cadmium-containing wastewater.

Citation Information

Cited By

  • Phosphorus-doped biochar material, preparation method and application of phosphorus-doped biochar material in water treatment

    CN121060608A